2023
DOI: 10.1111/mec.16989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms ofEda‐mediated adaptation to freshwater in threespine stickleback

Abstract: A main goal of evolutionary biology is to understand the genetic basis of adaptive evolution. Although the genes that underlie some adaptive phenotypes are now known, the molecular pathways and regulatory mechanisms mediating the phenotypic effects of those genes often remain a black box. Unveiling this black box is necessary to fully understand the genetic basis of adaptive phenotypes, and to understand why particular genes might be used during phenotypic evolution. Here, we investigated which genes and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…We found 1852 DEGs, 109 DSGs and 30 DESGs (Figure 2a). This disparity in abundance of DEGs and DSGs is a pattern commonly found in other studies (Grantham and Brisson 2018;Jacobs and Elmer 2021;Steward et al 2022;Rodríguez-Ramírez et al 2023), though not always (Singh et al 2017).…”
Section: Over One Hundred Genes Have Changes In Alternative Splicing ...supporting
confidence: 80%
See 1 more Smart Citation
“…We found 1852 DEGs, 109 DSGs and 30 DESGs (Figure 2a). This disparity in abundance of DEGs and DSGs is a pattern commonly found in other studies (Grantham and Brisson 2018;Jacobs and Elmer 2021;Steward et al 2022;Rodríguez-Ramírez et al 2023), though not always (Singh et al 2017).…”
Section: Over One Hundred Genes Have Changes In Alternative Splicing ...supporting
confidence: 80%
“…Methods based on differential exon usage have been used in other studies (e.g. Singh et al, 2017; Jacobs & Elmer 2021; Rodríguez-Ramírez et al, 2023) and can use most of the same reads as DE analyses but cannot detect certain types of splicing (i.e. A3SS and A5SS).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified Bmp2k on LG13 as a candidate gene that impacts plate number variation in the nine-spined stickleback, and Bmp7 on LG17 as a gene that potentially influences both plate number and plate width (although not plate area or height). Similarly, a recent study in the three-spined stickleback also found that the BMP pathway is a strong candidate mediating the effect of Eda on the development of lateral plates (Rodríguez-Ramírez et al 2023). However, as all of the QTL regions in our study included tens to hundreds of genes, little confidence can be assigned to the identified candidate genes.…”
Section: Discussionmentioning
confidence: 47%
“…In the butterfly Bicyclus anynana more than half of the genes that were differentially expressed were also differentially spliced but none of the genes associated with seasonal plasticity were differentially expressed and alternatively spliced ( Steward et al 2022 ). Similarly a recent study on the Eda haplotype in sticklebacks found only a small overlap (six genes) of gene expression and alternative splicing, but a lot of differentially spliced genes (no significant enrichment) were involved in the same biological processes as the differentially expressed ones ( Rodríguez-Ramírez et al 2023 ).…”
Section: Distinct Roles Of Gene Expression and Alternative Splicing D...mentioning
confidence: 90%